Using A Situation Analysis To Identify The Construction Industry Deficiencies In Botswana - Kaggwa, Joseph Ssegawa; Ngowi, Alfred B.; Ntshwene, Keneilwe (Penerbit Universiti Sains Malaysia, 2013)
This paper reports the results of a multi-phase study aimed at identifying ways of transforming the construction industry in Botswana into an efficient, effective and sustainable sector. The study examined a number of reports indicating that public construction projects were not delivered as contractually expected. The first phase of the study, a situation analysis, was divided into two stages, with the first validating the claims that projects perform poorly in terms of both time and cost. Project data were compiled and analysed by computing the cost and time variances. The second stage solicited the opinions of various industry stakeholders regarding the deficiencies in the industry that led to poor project performance. Based on 323 sampled public construction projects, the results indicated that 13% had been abandoned and retendered. For those projects not abandoned, 52% and 75% had cost and time overruns, respectively. On average, the amount of cost overruns was 15% while the amount of time overruns was 75%. This level of performance is considered worrisome if allowed to continue. Causes of the overruns were identified as emanating from the decisions and actions of clients, suppliers, and regulators as well as the lack of a coherent facilitation of the construction business environment. The latter was singled out as an urgent challenge that needs addressing if the construction industry is to exist as a sustainable sector in Botswana. Though the concept of construction industry development is not new, this paper underscores that situations for each country are different and models that aim to transform an industry must look at the underlying context of the sector. With the exception of one study, no other extensive empirical study has been conducted in Botswana to identify and document deficiencies leading to the poor delivery of public construction projects. These findings also provide a generic approach to transforming the construction industry